1996
DOI: 10.1093/oxfordjournals.humrep.a019151
|View full text |Cite
|
Sign up to set email alerts
|

Uterus and endometrium: Effects of daily low dose mifepristone on endometrial maturation and proliferation

Abstract: Following an ovulatory control cycle, six women took 2 mg of mifepristone daily for 30 days. Endometrial biopsies were collected in the control cycle between 7 and 11 days after the plasma luteinizing hormone (LH) surge and on the corresponding day of the treatment cycle (days 19-28). In order to investigate the effects of unopposed oestrogen on the endometrium, persistent proliferative endometrium was obtained from six women with anovulatory infertility due to polycystic ovarian syndrome (PCOS) on a similar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 0 publications
1
35
1
3
Order By: Relevance
“…It has been reported that postcoital administration of mifepristone modulates egg transport through the oviduct (Roblero, et al, 1987;Fuentealba, et al, 1987;Yang and Wu, 1990), retards early embryonic development (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991), delays endometrial maturation (Roblero and Croxatto, 1991;Batista, et al, 1992;Cameron, et al, 1996) and thereby inhibits or delays implantation (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991;Dao, et al, 1996). In the present study, treatment with 4 mg/kg mifepristone during the post-coital phase produced small numbers of live embryos and a high postimplantation embryonic mortality but did not reduce the number of implantations.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been reported that postcoital administration of mifepristone modulates egg transport through the oviduct (Roblero, et al, 1987;Fuentealba, et al, 1987;Yang and Wu, 1990), retards early embryonic development (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991), delays endometrial maturation (Roblero and Croxatto, 1991;Batista, et al, 1992;Cameron, et al, 1996) and thereby inhibits or delays implantation (Psychoyos and Prapas, 1987;Roblero and Croxatto, 1991;Dao, et al, 1996). In the present study, treatment with 4 mg/kg mifepristone during the post-coital phase produced small numbers of live embryos and a high postimplantation embryonic mortality but did not reduce the number of implantations.…”
Section: Discussioncontrasting
confidence: 50%
“…Some PRMs exert anti-estrogenic effects, either through partial progesterone receptor agonist activity, 6,7 or, exert these effects independently of the progesterone receptor itself, that is by upregulation of the androgen receptor response. 8,9 These PRM effects are evident as dose-dependent suppression of estrogen-induced mitotic activity, [10][11][12] and appearance of glandular secretory changes. 7 Assessment of PRM induced changes in the endometrium by pathologists is not only a prerequisite step to determine suitability for widespread clinical use, but also indicates how community pathologists are likely to respond to endometrial biopsies from women on these agents.…”
mentioning
confidence: 99%
“…Access to material is generally confined to individuals involved in ongoing clinical trials, members of the parent pharmaceutical companies, a few researchers, and regulatory agencies. Now that the histological features referable to PRM administration are starting to emerge, 7,[12][13][14][15] there are unanswered questions of how they relate, if at all, to known diagnostic entities such as endometrial hyperplasia.…”
mentioning
confidence: 99%
“…Low doses of RU486 administered chronically to women also inhibited glandular mitosis and induced stromal compaction in the endometrium (Cameron et al, 1996). Anti-proliferative and apoptotic effects of anti-progestins have also been observed in vitro in various breast cancer cell lines, and these effects have been referred to as receptor-mediated 'cytostatic and cytotoxic' effects.…”
Section: Endometrial Anti-proliferative Effects Of Antiprogestins In mentioning
confidence: 99%
“…Such chronic, low dose treatment suppresses endometrial maturation and makes successful implantation unlikely (Batista et al, 1992;Cameron et al, 1996). The third group consisted of women who were treated with 200 mg oral mifepristone (or vehicle) 2 days after the ovulatory surge of LH and sampled 4-6 days later.…”
Section: Is the Androgen Receptor Involved In The Endometrial Anti-prmentioning
confidence: 99%